Civic communicators' view of and approach to health promotion for newly arrived migrants in Sweden - Sara Svanholm; Heidi Carlerby; Eija Viitasara (Frontiers Media S.A., 2022)
For newly arrived migrants, integration is important in promoting health and decreasing health inequities. In a Swedish context, civic orientation is a program to promote integration and increase the chance of employment for newly arrived migrants. The aim of this project was to explore how civic communicators view and approach health promotion in their work with newly arrived migrants in the civic orientation program in Sweden. Data were collected through interviews with eight civic communicators working with newly arrived migrants in civic orientation in the north of Sweden. The interviews followed a semi-structured interview guide and were transcribed verbatim and analyzed using thematic analysis. The analysis resulted in the main theme "To dress the participants for a (healthy) life in Sweden," with two sub-themes "Knowledge-a key to health" and "Being a guide for participants in a new context." In their work with civic orientation for newly arrived migrants, civic communicators are involved in health promotion by preparing their participants for a life in Sweden. They work to empower their participants to be able to make informed decisions and live healthy lives by both providing information to enhance knowledge and skills. They also work to guide them through the complexity of being in a new situation and country.